Transportation biofuels : pathways for production - Hoogendoorn, Alwin; Kasteren, Han van (Green chemistry series ;, 2020)
Biofuels produced from renewable resources offer a more sustainable alternative to fossil fuels. The new edition of this book provides updates on the previously discussed pathways for transportation biofuels.